Nexus Between Industrialization and Greenhouse Gas Emissions: Impacts on Infant Mortality in Lower-Middle-Income Countries (Journal of Asian Development Studies, 2023)
The study examines how industrialization, income distribution, and other socio-economic factors play crucial roles in influencing mortality rates and demographic patterns. This study used a strong, balanced panel dataset and covered 37 lower-middle-income countries. The econometrics approach DOLS used, as well as two models. The study provides mixed results for both models. In model 1, morality rate is a dependent variable, while other independent variables. In the model, greenhouse gases and urbanization both have a negative and statistically significant impact on morality rates. In Model 2, urbanization and adjusted national income level have a negative impact on the total adult mortality rate. Besides, greenhouse gases and renewable energy have a positive impact on the total adult mortality rate. The study recommends deep attention to environmental protection and adopting clean energy in lower-middle-income countries to alleviate the adverse effects of greenhouse gas emissions, industrialization, and nonrenewable energy usage on human health.